INDONESIAN UNDERGRADUATE STUDENTS’ PERCEPTIONS OF PLAGIARISM: A SURVEY STUDY - Umi Sismia Wardani; Ista Maharsi (STKIP Siliwangi, 2023)
This study aimed to identify Indonesian undergraduate students' perceptions of plagiarism in an English language education department at a private university in Indonesia. This method in this study is a survey study and the instrument in this study used a questionnaire, which means is quantitative research. The data were collected using a 22-item questionnaire on plagiarism awareness adapted from Jereb et al. (2018). One hundred three students taking Academic Reading and Writing classes participated in this study. The students who filled out the questionnaire on Google Forms used 5 – a point Likert scale to respond to the statement. It can be seen the results of the data from five aspects. The highest score belongs to the awareness of plagiarism (M= 4.2; SD= 1.138). The second-highest score belongs to the aspects of plagiarism knowledge (M= 3.12; SD= 1.118). The third-highest score is the attitude towards plagiarism (M= 2.45; SD= 1.012). The fourth-highest score belongs to the aspects of acceptability of plagiarism (M= 2.38; SD= 1.032). Then, the lowest mean score belongs to the unknowingness of plagiarism (M= 2.18; SD= 1.092). The findings showed that most students are aware of plagiarism, although plagiarism is wrong. Plagiarism occurs due to several demands from teachers or institutions; another plagiarism factor is a lack of knowledge about plagiarism.